2018
DOI: 10.22452/ajba.vol11no1.9
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Theory of Planned Behaviour: Impact of Past Behavioural Biases on the Investment Decision of Indian Investors

Abstract: Manuscript type: Research paper. Research aims: This paper aims to investigate the applicability of the Theory of Planned Behaviour (TPB) in examining individuals' behavioural intention to invest in the capital market. This study extends on the TPB model by considering the role of past behavioural biases (PBB) as a factor in influencing the individuals' behavioural investment intentions. Design/ Methodology/ Approach: This paper employs a hypothesis deductive approach. The research model is tested through stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 53 publications
9
68
0
10
Order By: Relevance
“…Subjective norms are influenced by various parties related to the individual concerned. Related parties become a source of reference in making decisions (Raut et al, 2018). These parties can come from colleagues, family and financial expert opinion.…”
Section: Fig 2 Research Results Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective norms are influenced by various parties related to the individual concerned. Related parties become a source of reference in making decisions (Raut et al, 2018). These parties can come from colleagues, family and financial expert opinion.…”
Section: Fig 2 Research Results Modelmentioning
confidence: 99%
“…Scholars as the younger generation who also play a role in the development of economic activities in the future, so it is necessary to know the interest of scholars in purchasing shares. Research Raut et al, (2018) revealed that stock purchases can be influenced by attitudes, subjective norms, behavioral control, and past experience bias. The act of investing is also related to the interest in investing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that an individual's investment behaviour is associated with risk attitude (Annamalah et al, 2019;Gakhar, 2019;Kemp, Chan, Chen, & Helton, 2018). Raut, Das, and Kumar (2018) found attitude towards risk to be the most significant predictor for the investment intention of Indian investors. Those who could afford to lose and were willing to take financial risks had favourable attitudes towards investment and were more likely to invest (Raut, Das, & Kumar, 2018).…”
Section: Previous Studymentioning
confidence: 95%
“…Raut, Das, and Kumar (2018) found attitude towards risk to be the most significant predictor for the investment intention of Indian investors. Those who could afford to lose and were willing to take financial risks had favourable attitudes towards investment and were more likely to invest (Raut, Das, & Kumar, 2018). Gakhar (2019) noted that risk attitude has a significant difference in medium-risk investment instruments taken by investors.…”
Section: Previous Studymentioning
confidence: 95%
“…Previous studies have shown that attitude towards a financial product (e.g. Sukuk) have a positive impact on investors' intention (Ashidiqi, & Arundina, 2017;Raut, Das, & Kumar, 2018) and intention to use sukuk (Warsame, & Ireri, 2016). The researchers strongly argued that attitude is one of the important factors that influences the intention of an investor.…”
Section: Attitude Towards Investment In Islamic Sukuk and Intention Tmentioning
confidence: 99%